Antimicrobial and cytotoxic activities of Barleria prionitis and Barleria grandiflora: A comparative study (Bangladesh Journal of Pharmacology, 2016)
Leaf juices as well as leaves of Barleria prionitis and Barleria grandiflora are being used by rural people across various regions of India in the treatment of oral ailments such as dental troubles, gum ailments, pyorrhoea, dental carries and mouth ulcers. Zone of inhibition and MIC values obtained for all the extracts suggest ethanolic extract of the herbs were more antimicrobial when compared to the aqueous extract. Results of biofilm suppression were found statistically significant (p